1997
DOI: 10.1111/j.1740-8261.1997.tb01601.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prepuberal and Postpuberal Gonadectomy on Radial Physeal Closure in Male and Female Domestic Cats

Abstract: Male (n = 6/group) and female (n = 6/group) kittens were gonadectomized at 7 weeks (prepuberally) or 7 months of age (postpuberally), or left intact. Lateral radiographic projections of the right forelimb were made from 4 months of age until the distal radial physis was closed, or 24 months of age. In males, distal radial physeal closure was delayed in both groups of gonadectomized animals, compared to intact males (p < 0.01). In females, proximal radial physeal closure was significantly delayed in prepuberall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0
9

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(129 citation statements)
references
References 17 publications
5
111
0
9
Order By: Relevance
“…Earlier research has indicated that an estimated 20% to 30% reduction in food intake is needed to maintain BW of neutered cats (Flynn et al, 1996;Root et al, 1996;Belsito et al, 2009). Therefore, BW gain following ovariohysterectomy is not only due to increased food intake, but may also be due to a lower metabolic rate and decreased physical activity.…”
Section: High-protein Diet Following Ovariohysterectomymentioning
confidence: 99%
“…Earlier research has indicated that an estimated 20% to 30% reduction in food intake is needed to maintain BW of neutered cats (Flynn et al, 1996;Root et al, 1996;Belsito et al, 2009). Therefore, BW gain following ovariohysterectomy is not only due to increased food intake, but may also be due to a lower metabolic rate and decreased physical activity.…”
Section: High-protein Diet Following Ovariohysterectomymentioning
confidence: 99%
“…The reduction in opportunities for physical activity would be compounded when cats are housed indoors in a single cat or two cat household without a dog. In addition, there is possibly an interaction between these environmental factors and reproductive status as, compared to intact cats, neutered cats are more sedentary (Hart et al 1973;Belsito et al 2009) and therefore may be predisposed to obesity due to decreased energy expenditure combined with reduced maintenance energy requirements (Root et al 1996;Fettman et al 1998;Mitsuhashi et al 2011). …”
Section: Environmental Factorsmentioning
confidence: 99%
“…Neutering decreases the metabolic rate and calorie requirement of cats, which may then lead to an accumulation of adipose tissue (Flynn et at. 1996;Root et al 1996;Fettman et al 1998;Mitsuhashi et al 2011). When 22 shorthair adult female cats were fed at maintenance energy requirements for intact cats before and after ovariohysterectomy, all the cats increased body weight by 16% and BCS by one point after ovariohysterectomy (Mitsuhashi et al 2011).…”
Section: Sex and Reproductive Statusmentioning
confidence: 99%
“…Neutering before physeal closure and overweight or obesity have been cited as factors that contribute to the disease (McNicholas et al 2002). Retardation of the physeal closure occurs when gonadectomy is performed prior to seven months of age (Root et al 1997). However, delayed physeal closure due to early gonadectomy is not associated in all cases, since the disease has occurred in intact males (Craig 2001;Burke 2003).…”
mentioning
confidence: 99%